Correlation between Soil Organic Matter, Total Organic Matter and Water Content with Climate and Depths of Soil at Different Land use in Kelantan, Malaysia - A Azlan; ER Aweng; CO Ibrahim; A Noorhaidah (Journal of Applied Sciences and Environmental Management)
A total of four sites distributed in different soils of Kelantan State, Malaysia was identified for the study. Soils were collected by depth interval of 0-10cm, 10-20cm and 20-30cm. The correlation of soil organic matter (SOM) content, total organic carbon (TOC) content, water content and soils texture for industrial area at Pengkalan Chepa, township of Kota Bharu district, agricultural area at Banggu and forested area in UMK, Jeli were investigated. These data sets were also correlated to temporal event in Kelantan State. Correlation analysis indicated that,generally, SOM and TOC concentration and soil classes had a positive correlation with temporal patterns and no significance effects with depth of the soils. The relationships between SOM content, TOC content and clay + silt content, were also studied. The results showed that, SOM concentration was lower (P < 0.05) at Pengkalan Chepa area (1.96%) compared to Kota Bharu (2.06%), Banggu (2.77%) and Jeli (7.39%). At the same time, the TOC level also showed that Banggu area recorded the lowest concentration (0.42%) followed by Kota Bharu (0.71%), Pengkalan Chepa (0.76%) and Jeli (3.73%). The temporal factor (p < 0.05) showed that TOC content higher during dry season (1.76%) and lower during pre monsoon (0.48%) and lowest in monsoon season (0.25%). Similar results were obtained for SOM content, higher during dry season (4.00%) followed by pre monsoon (2.12%) and lowest in monsoon season (1.67%). The lowest TOC and SOM content in soil during monsoon season was believed to be due heavy rain which detaches all the organic matter from soil particles into river.